Efektivitas Pengungkapan Corporate Social Responsibility, Leverage Operasi, Umur Perusahaan dan Tingkat Inflasi Terhadap Profitabilitas Perusahaan - Putu Purnama Dewi; I Dewa Gede Baswarasasika (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
This study aims to identify the effect of disclosure of Corporate Social Responsibility (CSR), Operating Leverage, Inflation Rate, Company Age towards the profitability of manufacturing sector of the 2017-2019 in Indonesian Stock Exchange (BEI) period. The number of sample in this research are 26 manufacturing companies in the consumer good listed in BEI in 2017-2019, The analytical techniques utilized in this study is multiple linear regression analysis. The outcome of this research is illustrate about the CSR significantly effects the probability of these companies as seen from the assessment of the CSR indicators which were relatively good from each category (Economy, Environment, Social, Human Rights, Society, and Responsibility for the Product), Operating Leverage, asset, equity possessed have immense effect on the growth of profitability, Inflation and company age rate seen from t result has no affect on profitability.